Organic and inorganic compounds as corrosion inhibitors to reduce galvanic effect for the hybrid structure AA2024-CFPR - Roy López-Sesenes (International Association of Physical Chemists (IAPC), 2021)
The effect of the galvanic corrosion process taking place between aluminium alloy (AA2024-T3) and carbon fiber reinforced plastic (CFRP) immersed in 0.05 M NaCl was studied using organic and inorganic compounds as corrosion inhibitors. Electrochemical approaches such as electrochemical noise analysis (ENA) and electrochemical impedance spectroscopy (EIS) were carried out to evaluate efficiencies of 1,2,4-triazole (C2H3N3) and cerium nitrate hexahydrate (Ce(NO3)3·6H2O) as corrosion inhibitors. The highest efficiency was reached for Ce(NO3)3.6H2O, with some improvement observed by adding C2H3N3 in a mixed inhibitor solution. The noise resistance (Rn) and polarization resistance (Rp) values calculated from ENA and EIS data showed almost identical behavior with different magnitudes but similar trends. Adsorption isotherm models estimated with fractional surface coverage (q) parameter were fitted better to Langmuir model for C2H3N3 and Temkin model for Ce(NO3)3·6H2O. The calculated values of Gibbs free energy suggested physisorption and chemisorption as spontaneous interactions between a metal surface and both inhibitors. Energy-dispersive X-ray spectroscopy (EDS) was carried out before and after immersing AA2024-T3 in the electrolyte, identifying rich zones in copper with cerium deposited over it and confirming the presence of rare-earth oxide deposition and oxide film products. The EDS analysis for CFRP revealed the deposition of Ce and Al particles over its surface after immersion in the electrolyte, especially in the areas rich in carbon.